Magnetic resonance elastography with guided pressure waves. (24th February 2022) - Tardieu, Marion; Salameh, Najat; Souris, Line; Rousseau, David; Jourdain, Laurène; Skeif, Hanadi; Prévot, François; de Rochefort, Ludovic; Ducreux, Denis; Louis, Bruno; Garteiser, Philippe; Sinkus, Ralph; et al.
Abstract : Magnetic resonance elastography aims to non‐invasively and remotely characterize the mechanical properties of living tissues. To quantitatively and regionally map the shear viscoelastic moduli in vivo, the technique must achieve proper mechanical excitation throughout the targeted tissues. Although it is straightforward, ante manibus, in close organs such as the liver or the breast, which practitioners clinically palpate already, it is somewhat fortunately highly challenging to trick the natural protective barriers of remote organs such as the brain. So far, mechanical waves have been induced in the latter by shaking the surrounding cranial bones. Here, the skull was circumvented by guiding pressure waves inside the subject's buccal cavity so mechanical waves could propagate from within through the brainstem up to the brain. Repeatable, reproducible and robust displacement fields were recorded in phantoms and in vivo by magnetic resonance elastography with guided pressure waves such that quantitative mechanical outcomes were extracted in the human brain. Abstract : Magnetic resonance elastography (MRE) aims to map mechanical properties of living tissues by measuring their mechanical response to an external excitation. MRE is challenging in remote organs such as the lung or the brain because of natural protective barriers. We developed original means of mechanical excitation using natural pathways to guide pressure waves deep inside the body. Here, we show in the human brain that MRE is repeatable, reproducible and robust with guided pressure waves up to 235 Hz.